2020
DOI: 10.1111/php.13224
|View full text |Cite
|
Sign up to set email alerts
|

Light Fluence Rate and Tissue Oxygenation (StO2) Distributions Within the Thoracic Cavity of Patients Receiving Intraoperative Photodynamic Therapy for Malignant Pleural Mesothelioma

Abstract: The distributions of light and tissue oxygenation (StO2) within the chest cavity were determined for 15 subjects undergoing macroscopic complete resection followed by intraoperative photodynamic therapy (PDT) as part of a clinical trial for the treatment of malignant pleural mesothelioma (MPM). Over the course of light delivery, detectors at each of eight different sites recorded exposure to variable fluence rate. Nevertheless, the treatment‐averaged fluence rate was similar among sites, ranging from a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[98][99][100] Furthermore, many dosimetry methods have already been investigated and integrated into the treatment platform. These dosimetry methods have included measuring photofrin photobleaching, 100 ROS production, 98 and light fluence, to name a few. 99,101 For this indication, IPDT could play a further role in treatment and possibly expand the number of treatment sessions or lengthening the treatment out beyond just using IPDT as an adjunct treatment postsurgery.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[98][99][100] Furthermore, many dosimetry methods have already been investigated and integrated into the treatment platform. These dosimetry methods have included measuring photofrin photobleaching, 100 ROS production, 98 and light fluence, to name a few. 99,101 For this indication, IPDT could play a further role in treatment and possibly expand the number of treatment sessions or lengthening the treatment out beyond just using IPDT as an adjunct treatment postsurgery.…”
Section: Other Applicationsmentioning
confidence: 99%
“… 97 PDT has been used previously with success in small clinical trials. 98 100 Furthermore, many dosimetry methods have already been investigated and integrated into the treatment platform. These dosimetry methods have included measuring photofrin photobleaching, 100 ROS production, 98 and light fluence, to name a few.…”
Section: Applications and Challenges For Interstitial Photodynamic Therapymentioning
confidence: 99%
“…Creative direct and (mostly) indirect measurements have been developed to navigate the treatment process [7][8][9]. Among current methods, it can merely measure the fluorescence intensity [10,11] or might require the comprehensive measurement of many relevant parameters in the surgical procedure of clinical studies [12]. In practice, most clinical PDT procedures around the world only involve the calculation of drug dose and delivered light dose at the lesion surface.…”
Section: Dosimetry Study In Photodynamic Therapy For Diagnosis Precimentioning
confidence: 99%
“…Lietke et al used a similar approach in designing treatment plans for malignant glioma recurrences 13 . In the context of a larger body space, Dupre et al reported on the performance of surface contact spatially-resolved diffuse reflectance spectroscopy prior to PDT of the pleural cavity 14 . These measurements, along with real-time fluence monitoring 15 , were used to deliver uniform light doses to highly heterogeneous subjects.…”
Section: Introductionmentioning
confidence: 99%